2016
DOI: 10.1111/cogs.12399
|View full text |Cite
|
Sign up to set email alerts
|

The Episodic Nature of Experience: A Dynamical Systems Analysis

Abstract: Context is an important construct in many domains of cognition, including learning, memory, and emotion. We used dynamical systems methods to demonstrate the episodic nature of experience by showing a natural separation between the scales over which within-context and between-context relationships operate. To do this, we represented an individual's emails extending over about 5 years in a high-dimensional semantic space and computed the dimensionalities of the subspaces occupied by these emails. Personal disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…Indeed it has been shown that reaction times between sequential trials show long-range correlations across a wide diversity of tasks (Palva and Palva, 2011;Thornton and Gilden, 2005). This is perhaps not surprising, given that, outside the scanner, human activity (Sreekumar et al, 2016;Sreekumar et al, 2014) and memory (Nielson et al, 2015) show a complex temporal structure that scales across many orders of magnitude. Detailed analyses of reaction time data in typical psychophysics experiments support the presence of a power law structure (Van Orden et al, 2005).…”
Section: Criticality In Brain and Behaviourmentioning
confidence: 98%
“…Indeed it has been shown that reaction times between sequential trials show long-range correlations across a wide diversity of tasks (Palva and Palva, 2011;Thornton and Gilden, 2005). This is perhaps not surprising, given that, outside the scanner, human activity (Sreekumar et al, 2016;Sreekumar et al, 2014) and memory (Nielson et al, 2015) show a complex temporal structure that scales across many orders of magnitude. Detailed analyses of reaction time data in typical psychophysics experiments support the presence of a power law structure (Van Orden et al, 2005).…”
Section: Criticality In Brain and Behaviourmentioning
confidence: 98%
“…Some studies have reported that the hippocampus is not involved in representing unitary items (e.g., Ross et al, 2017). Milivojevic et al (2016) suggested that the character and location hippocampal representations in their study may be abstracted versions of those items across multiple experiences over the course of the movie and therefore may behave more like a gist or lower-level context for those items.…”
mentioning
confidence: 85%
“…Most characters and locations are shared between the two narratives, and the narratives are interleaved in the movie, reducing confounds relating to temporal co-occurrence and visual similarity (both of which were further controlled for by statistical analyses). A whole-brain searchlight using representational similarity analysis (Kriegeskorte et al, 2008) revealed that hippocampal activity patterns differentiated between overall narrative contexts, as well as individual people and locations within those contexts. Furthermore, hippocampal activity corresponding to the two narratives gradually became more distinct over time.…”
mentioning
confidence: 99%
See 2 more Smart Citations